Evaluasi Klinik Autorefraktor NIDEK TONOREF III Dibandingkan dengan Refraksi Subjektif pada Populasi Miopia Muda - Vera Sumual; Ade J. Nursalim; Stevanus Paliliewu; Andrew Citra; Mochamad Sahroni; Dian Anggraini; Burhan Noho (e-CliniC, 2023)
Abstract: Incidence of myopia has continued to increase in the last few decades and is expected to increase continually from time to time. Early detection of myopia is expected to prevent the occurrence of amblyopia, strabismus or other eye disorders. Autorefractor is a medical device that can be used before refraction examination in order to increase the efficiency in measurement of refractive disorders. However, the autorefractor used needs to be tested first to ensure the reliability of the tool in supporting clinical examinations. This study aimed to evaluate the reliability of the NIDEK TONOREF III autorefractor in daily clinical practice in young myopia population. The results obtained 42 subjects with myopic refractive error aged 20-41 years. The majority were females and had mild myopia. The statistical analysis showed no significant difference in the calculation of pupillary distance (p=0.581) and the correction results (p=0.842) between autorefractor and subjective refraction. In conclusion, the NIDEK Tonoref III autorefractor exhibits a high degree of reliability in evaluating glasses prescription and pupillary distance for cases of myopia. Keywords: autorefractor; myopia; NIDEK TONOREF III; objective refraction; subjective refraction   Abstrak: Angka kejadian miopia terus mengalami peningkatan dalam beberapa dekade terakhir dan diperkirakan akan terus bertambah. Deteksi dini miopia diharapkan dapat mencegah terjadinya ambliopia, strabismus ataupun kelainan mata lainnya. Autorefraktor merupakan alat pemeriksaan yang dapat digunakan mendahului pemeriksaan refraksi untuk meningkatkan efisiensi pemeriksaan kelainan refraksi. Namun, autorefraktor yang digunakan perlu diuji terlebih dahulu sehingga menjamin keterandalan alat dalam menunjang pemeriksaan klinis. Penelitian ini bertujuan untuk menguji keterandalan autorefraktor NIDEK TONOREF III dalam praktik klinis sehari-hari pada populasi miopia muda. Hasil penelitian mendapatkan 42 subjek penelitian dengan kelainan refraksi miopia pada rentang usia 20-41 tahun. Subjek terbanyak berada pada kategori miopia ringan dan berjenis kelamin perempuan. Hasil uji t-independen menunjukkan tidak terdapat perbedaan bermakna pada perhitungan jarak antar pupil (p=0,581) serta hasil koreksi (p=0,842) antara autorefraktor dan refraksi subjektif. Simpulan penelitian ini ialah autorefraktor NIDEK Tonoref III memiliki keterandalan yang baik dalam menilai koreksi kacamata dan jarak antar pupil untuk kasus miopia. Kata kunci: autorefraktor; miopia; NIDEK TONOREF III; refraksi objektif; refraksi subjektif